Excitons in conjugated polymers: a tale of two particles. - Barford, W (2013)
Since the discovery of electroluminescence in the phenyl-based conjugated polymers in 1990, the field of polymer optoelectronics has matured to the extent that presently a wide class of devices have been commercialized. These range from both miniature and wide-area light emitting devices to hybrid photovoltaic devices. Similarly, our understanding of the fundamental processes that determine these optoelectronic properties has also progressed. In particular, owing to insights from both experimental and theoretical investigations, the role of the primary excited states, i.e., excitons, is now considerably clearer. This review discusses these primary excited states and explains how the three key roles of electron-electron interactions, electron-nuclear coupling, and disorder determine their properties. We show that the properties of an exciton are more readily understood by decomposing it into two effective particles. First, a relative particle that describes the size and binding energy of the electron-hole pair. Second, a center-of-mass particle that describes the extent of the delocalization of the electron-hole pair. Disorder and coupling to the normal modes localizes the center-of-mass particle and provides a quantitative definition of chromophores in conjugated polymers, paving the way for a first-principles theory of exciton diffusion in these systems.